Truly bewept, full of strife - Kocijančič, Matic (Clotho, 2021)
In postwar Western culture, the myth of Antigone has been the subject of noted literary, literary-critical, dramatic, philosophical, and philological treatments, not least due to the strong influence of one of the key plays of the twentieth century, Jean Anouilh’s Antigone. The rich discussion of the myth has often dealt with its most famous formulation, Sophocles’ Antigone, but has paid less attention to the broader ancient context; the epic sources (the Iliad, Odyssey, Thebaid, and Oedipodea); the other tragic versions (Aeschylus’s Seven Against Thebes and his lost Eleusinians; Euripides’s Suppliants, Phoenician Wome n, and Antigone, of which only a few short fragments have been preserved); and the responses of late antiquity. This paper analyses the basic features of this nearly thousand-year-long ancient tradition and shows how they connect in surprising ways – sometimes even more directly than Sophoclean tragedy does – with the main issues in some unique contemporary traditions of its reception (especially the Slovenian, Polish and Argentine ones): the question of burying the wartime (or postwar) dead and the ideal of reconciliation.
Keywords: Aeschylus; Antigona; Antigonin mit; Euripides; Homerus; literarne študije; Sophocles; starogrška književnost